2018
DOI: 10.1007/s00296-018-4103-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of energy metabolism in the growth plate and osteoarthritic chondrocytes

Abstract: Osteoarthritis (OA) is a chronic disorder associated mainly with pain, limited range of motion, stiffness, low-grade systemic inflammation, and articular cartilage destruction. Recent studies have demonstrated the involvement of chondrocyte differentiation (hypertrophy) as one of the mechanisms in cartilage degradation in OA. This implicates the involvement of principal changes in the regulation of cellular function associated with profound alterations in chondrocyte energy metabolism in the course of cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 123 publications
3
34
0
3
Order By: Relevance
“…Meanwhile, an increase in oxidative phosphorylation was also be confirmed during aging to maintain ATP production. Similar phenomenon also occurs in hypertrophic chondrocytes, that hypertrophic chondrocytes rely more on mitochondrial respiration specifically in hypertrophic zone of the growth plate, as well as in OA cartilage 25,26 . Further, no significant differences in cellular senescence related changes were found, as we demonstrated that mitochondrial dysfunction contributed to metabolic disorders above all, it would not be unreasonable to assume that age-related mitochondrial dysfunction was prior to cellular senescence and might contribute to normal aging as well as OA 27,28 .…”
Section: Osteoarthritis Andcartilagesupporting
confidence: 57%
See 1 more Smart Citation
“…Meanwhile, an increase in oxidative phosphorylation was also be confirmed during aging to maintain ATP production. Similar phenomenon also occurs in hypertrophic chondrocytes, that hypertrophic chondrocytes rely more on mitochondrial respiration specifically in hypertrophic zone of the growth plate, as well as in OA cartilage 25,26 . Further, no significant differences in cellular senescence related changes were found, as we demonstrated that mitochondrial dysfunction contributed to metabolic disorders above all, it would not be unreasonable to assume that age-related mitochondrial dysfunction was prior to cellular senescence and might contribute to normal aging as well as OA 27,28 .…”
Section: Osteoarthritis Andcartilagesupporting
confidence: 57%
“…Chondrocytes, which rely on glycolysis to generate ATP for cellular energy 23 , may increase oxygen consumption as a compensatory way to maintain ATP production through the MRC when glycolysis is inhibited for any reason 24,25 . Energy metabolic homeostasis between glycolysis and oxidative phosphorylation in chondrocytes is critical for cellular survival and for maintaining extracellular matrix production 26 .…”
Section: Parkin May Regulate Mfn2 Expression During Aging and Oamentioning
confidence: 99%
“…In addition to a potential primary role of hypoxia in the development of the histopathologic growth plate changes, hypoglycaemia may also play an important role. The growth plate is a highly metabolic tissue, relying on anaerobic glycolysis 37 , and glucose serves as an essential source of energy 38 . Consequently, central chondrocytes may die due to glucose insufficiency and impaired glycolysis decreasing the energy supply.…”
Section: Discussionmentioning
confidence: 99%
“…В связи с этим терапия должна приводить к общей нормализации метаболизма клеток всего организма [143]. Экспрессия генов является наиболее ранним ответом организма на изменения внешней и внутренней среды клетки задолго до изменения экспрессии соответствующих белков на тканевом и организменном уровнях [13] и поэтому может быть использована для экспресс-оценки состояния больного РЗ. Более того, изменения, происходящие в тканях и крови больных РА взаимосвязаны, поскольку показано, что в клетках крови больных РА повышена экспрессия генов, регулирующих морфогенез кости и хряща, по сравнению со здоровыми лицами [144] и отмечена корреляция экспрессии генов в крови и повреждённых тканях больных РА [145][146][147][148].…”
Section: анализ экспрессии генов в крови как инструмент персонифицироunclassified
“…Напротив, анализ экспрессии генов в мононуклеарных клетках периферической крови может быть более адекватным подходом для идентификации биомаркеров для персонифицированной терапии вследствие системной природы РЗ [1]. Кроме того, поскольку экспрессия генов является наиболее ранним маркером изменений организма в ответ на заболевание или терапию [13], идентификация генов, контролирующих процессы развития заболевания и его терапии, может служить прогностическим инструментом в клинической практике.…”
Section: Introductionunclassified